CARACTERÍSTICAS AGRONÔMICAS E FORRAGEIRAS DE TRIGO DUPLO PROPÓSITO SUBMETIDO A SISTEMAS DE CORTE NA CV. BRS UMBU - Carletto, Rodolfo (2013)
The experiment was conducted at the Núcleo de Produção Animal (NUPRAN) Universidade Estadual do Centro Oeste (UNICENTRO), with the objective to evaluate biomass production and nutritional value of the forage of wheat dual purpose in cutting systems: T1- without cut (control), T2- one cut and T3- two cuts. The cumulative production of green biomass production reached an average of 21.913 kg ha?¹ for the treatment without cut 14.625 kg ha?¹ for treatment with a cut and 5294 kg ha?¹ for treatment with two cuts has to the production of dry biomass accumulation observed were the average of 10.926 kg ha?¹ for the treatment blunt, 7989 kg ha?¹ for the treatment of a cut and 3514 kg ha?¹ for the treatment with two cuts. The production of stems and leaves showed to be influenced by management cuts, where values were higher for the second evaluation of cutting forage at 105 DAP. For evaluating the nutritive value composition no significant differences (P>0.05) for the variables, crude protein, acid detergent fiber, neutral detergent fiber, hemicellulose, total digestible nutrients, dry matter intake per body weight values were found on food and net energy of lactation. Only the content of mineral matter and the estimated value for milk production were statistical differences between treatments. The wheat CV. BRS umbu shown to have good features to be used as dual-purpose cereal, but the cultivar is influenced by the management where the treatment of two cuts of forage presented lower values found in other treatments systems.